Feasibility Study of Homestay Management in Rural Villages (Tebat Meringang Lame, South Sumatra) - Wisanggeni Agus Priyanto; Andi Ade Zulkif; Hariman; Abdul Khaliq (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
This research aims to identify the current management conditions and assess the feasibility of developing homestays in Tebat Lereh Meringang Lame tourist village, South Sumatra. The research methodology involved interviews and observations with informants, including homestay managers and administrators of tourism awareness groups. The study revealed that only one person can manage each homestay in the tourist village. The same person may have multiple roles, such as receptionist, room attendant, and kitchen manager. The feasibility of developing homestays in the village depends on physical environmental conditions, such as landscape characteristics, cool air, and an authentic rural atmosphere, as well as the uniqueness of Ghumah Baghi architecture and the hospitality of Basemah Malay culture. It is recommended that the number of personnel in each homestay be increased according to workload standards. The required skills for this position include reception and room attendance, food management, and improving local literacy about Ghumah Baghi